Pemberian Makanan Tambahan (PMT ) Bubur Jewawut Di Wilayah Kerja Puskesmas Kumbe - Iksan, Muammar; Alimin; Andriadin; Auliah, Dwi Rezeki Auliah; Auliah, Indah Annisa; Wahyuningsi, Neneng Wahyuningsi (Journal of Excellence Humanities and Religiosity, 2025)
This community service activity aimed to address the nutritional problems of toddlers in the working area of the Kumbe Public Health Center through the utilization of local food resources, namely millet, as the basis for Supplementary Feeding (PMT). The importance of this topic is based on the high prevalence of nutritional problems in toddlers and the potential of millet as a nutrient-rich cereal. The community service method used was interactive counseling and focus group discussions with mothers of toddlers. The results of the activity showed a significant increase in mothers' knowledge and skills regarding balanced nutrition, the benefits of millet porridge as PMT, and how to process it. The positive reception of millet porridge as PMT indicates the potential for changes in feeding practices at home. In conclusion, this local food-based educational intervention is effective in increasing the capacity of mothers, which is an important initial step in efforts to improve the nutritional status of toddlers in the Kumbe Public Health Center area.